Does digitization improve green total factor energy efficiency? Evidence from Chinese 213 cities. (15th May 2022) - Gao, Da; Li, Ge; Yu, Jiyu
Abstract: The "Digital China" strategy is changing China's economic development model, and China is gradually shifting from pursuing rapid economic growth to high-quality economic development quality. This paper constructs China's urban information and communication technology (ICT) comprehensive development index and then innovatively undertakes the impact of the ICT on green total factor energy efficiency (GTFEE). Using panel data from China's 213 prefecture-level cities from 2011 to 2018, this study explores the direct impact, mediating effect, nonlinear relationship, and regional and development differences of ICT development on GTFEE. The dynamic panel model results show that ICT development positively promotes GTFEE, moderated by technological innovation and industrial structure effects. It is also indicated that the impact of ICT development on GTFEE varies with different resource mismatch levels by using the dynamic threshold model novelty. Moreover, diverse regional locations and development levels lead to varying influences of ICT development on GTFEE. Specifically, eastern regions and developed cities can benefit more from ICT development. Highlights: Constructing China's urban information and communication technology (ICT) index. ICT has a virtual promoting effect on green total factor energy efficiency (GTFEE). The mechanisms are technological innovation and industrial structure upgrading. The impact of ICT development on GTFEE varies with different resource mismatch. The GTFEE of eastern regions and developed cities can benefit more from ICT.